Anomie and Honor in the Albanian Society - Rira, Miranda (Richtmann Publishing, 2012)
This paper aims at elaborating and understanding anomie and the code of honor in the Albanian family. During the last twodecades, Albanians have experienced rapid changes, great turmoil and transitions from a communist, traditional ethnic-based societytowards a new era of modern norms of a â€œwesternâ€ society. Referring to Durkhemianâ€™s paradigm on anomie as the first leading cause tocrime and deviance will go further by explaining that when people are living in anomic state due to rapid changes in transitional societies,a revival of old canonical, patriarchal norms is seen which controls and constructs human behavior. In the Albanian psycho-socialsystem, the code of honor of Middle Ages is renewed, by influencing the level of crimes and homicides especially within the familymembers. We hypothesize that: â€œwhen ethnic-based family oriented societies face new rules and regulations, a deregulation of thesocial system and a disruption of family ties is displayed, hence a domain of anomie is created, a threat of collective conscience of thesociety, a state of being lost between past and future which influences people to be more prone to committing murder and crimestowards society, towards their families and towards themselves, committing suicide. The second hypotheses is that: the honor killingsare nothing but a rudiment of the old patriarchal societies and an expression of the collision between the new imposed norms and old,well-established traditions.